1991
DOI: 10.1007/bf00314786
|View full text |Cite
|
Sign up to set email alerts
|

Determination of erythrocyte-bound acetylcholinesterase activity for monitoring pyridostigmine therapy in myasthenia gravis

Abstract: Monitoring of pyridostigmine therapy in patients with myasthenia gravis is not routinely performed, since the daily pyridostigmine doses are adjusted to the patient's actual clinical status rather than to pyridostigmine plasma concentrations (PPC). Moreover, PPC determination is time-consuming and needs much technical equipment. Since pyridostigmine reversible blocks acetylcholinesterase (AChE) at the neuromuscular junction, we studied the correlation between the enzyme's blood activity (erythrocyte-bound AChE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

1996
1996
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
2
0
4
Order By: Relevance
“…Oral doses of pyridostigmine in MG patients typically range from 180 to 360 mg day −1 . In one report, the best effective stable dose of pyridostigmine for each patient was found to be that which reduced the individual's blood AChE activity by 45–65% (Henze et al 1991). We implanted subcutaneous minipumps to provide a steady infusion of pyridostigmine that reduced blood cholinesterase activity by a slightly lesser degree (39 ± 4% reduction).…”
Section: Discussionmentioning
confidence: 99%
“…Oral doses of pyridostigmine in MG patients typically range from 180 to 360 mg day −1 . In one report, the best effective stable dose of pyridostigmine for each patient was found to be that which reduced the individual's blood AChE activity by 45–65% (Henze et al 1991). We implanted subcutaneous minipumps to provide a steady infusion of pyridostigmine that reduced blood cholinesterase activity by a slightly lesser degree (39 ± 4% reduction).…”
Section: Discussionmentioning
confidence: 99%
“…Whole blood samples were used for this purpose, because acetylcholinesterase is highly expressed on the external membrane surface of erythrocytes 22,23 and because the activity of this enzyme has been found to decrease in patients during systemic exposure to anticholinesterase drugs. 23,24 Even if the use of erythrocyte acetyl-cholinesterase as a surrogate marker for the activity of acetylcholinesterase in the cholinergic nervous system has not been widely recognized, previous studies have shown that erythrocyte and neuronal acetylcholinesterase isoforms, which are all encoded by the same gene, display identical sensitivities toward inhibitory drugs. 25,26 Moreover, evidence has been provided that erythrocyte acetylcholinesterase activity significantly correlates with the activity of the same enzyme in human intestinal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Eine Korrelation der Plasmakonzentration zur klinischen Wirksamkeit ist daher nicht gegeben, Bestimmungen der Plasmaspiegel sind ohne besonderen therapeutischen Nutzen [31] . Gleiches gilt f ü r die Messung der Aktivit ä t der Acetylcholinesterase w ä hrend der Therapie mit Pyridostigmin [32] . Eine zus ä tzliche Therapie mit Ephedrin (2 × 25 mg / die), Kalium oder Spironolacton, wie fr ü her ü blich, ist heute aufgrund ihres zweifelhaften Eff ektes ohne Bedeutung, der Kaliumwert sollte jedoch hoch normal gehalten werden.…”
Section: Cholinesterasehemmstoff E Und 34-diaminopyridinunclassified